Risk factors for neuropathic pain in patients with knee osteoarthritis - ZHANG Yijing, ZHOU Xinjie, WANG Lei, FAN Kaiyong, LI Tieshan (精准医学杂志)
Objective To investigate the onset of neuropathic pain (NP) in patients with knee osteoarthritis (KOA) and related influencing factors. Methods A total of 313 KOA patients who attended the outpatient service of Department of Rehabi-litation Medicine in our hospital from July 2023 to October 2024 were enrolled, and according to the scoring results of the PainDETECT questionnaire, they were divided into NP group and non-NP group. The two groups were compared in terms of age, sex, body mass index (BMI), duration of knee pain symptoms, Kellgren-Lawrence (K-L) grading, pain Visual Analogue Scale (VAS) score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Hospital Anxiety and Depression Scale (HADS) score, and knee magnetic resonance imaging (MRI) findings. A logistic regression analysis was performed for the indicators with statistical significance identified by the univariate analysis to obtain the risk factors for NP. Results Of all patients, the patients with NP accounted for 16.61%. There were significant differences between the two groups in age, sex, pain VAS score, WOMAC, HADS score, and the proportion of patients with meniscus injury, soft tissue edema around the knee joint or knee joint ligament injury on MRI (H=16.272-49.953,χ2=12.897-23.792,P<0.05). The logistic regression analysis showed that old age, a high pain VAS score, a high HADS score, the presence of soft tissue edema around the knee joint, and the presence of knee joint ligament injury were risk factors for the onset of NP (P<0.05). Conclusion Old age, a high pain VAS score, a high HADS score, the presence of soft tissue edema around the knee joint, and the presence of knee joint ligament injury are risk factors for the onset of NP in KOA patients.